The Evaluation of the Relationship Between Oral Habits Prevalence and COVID-19 Pandemic in Adults and Adolescents: A Systematic Review - Amirhossein Mirhashemi; Mohammad Reza Khami; Mohammdjavad Kharazifard; Rashin Bahrami (Frontiers Media S.A., 2022)
Background and ObjectiveThe aim of this study was to systematically review the relationship between oral habits (bruxism- temporomandibular disorders) and COVID-19 pandemic in adults and adolescents.Method and MaterialA comprehensive search of the literature through PubMed, Scopus, Embase, google scholar and Cochrane databases was conducted. Such keywords as COVID-19, SARS-CoV-2, bruxism, adult, and adolescent were used.ResultsIn the initial search 818 articles were obtained; 68 cases were duplicates and excluded. By reviewing the article title, 714 articles were removed because they were not relevant to the topic. The remaining articles were reviewed, and studies that did not meet the inclusion criteria, as well as letter to editors and expert opinions were excluded. Finally, 11 articles were allowed to enter the study. Out of 11 related articles, 5 studies were excluded from the present study due to mismatch of the target population; and finally 6 articles were thoroughly reviewed.ConclusionStudies have shown that stress caused by the COVID-19 pandemic increases detrimental oral habits such as bruxism as well as temporomandibular disorders in adults and adolescents; In general, young single women are at high risk and more exposed to these harmful oral habits.